2022
DOI: 10.3389/feduc.2022.841395
|View full text |Cite
|
Sign up to set email alerts
|

Self-Regulated Writing of English Learners: Intervention Development

Abstract: The goal of this study was to develop and test an intervention in order to improve academic writing and SRL skills of English learners (ELs). ELs are well-represented across university and college campuses in the United States. While most of them thrive academically and receive their undergraduate and graduate degrees, a majority of ELs experience difficulties with academic writing such as limited English proficiency levels and opportunities to practice academic writing. Therefore, there is a need to develop a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 69 publications
2
9
0
Order By: Relevance
“…Differences in the use of self-regulated writing strategies between the high-and low-proficiency groups Some previous studies on the use of reflective writing have tended to hypothesize a potential influence of individual proficiency levels on observable SRL-related behaviors (Farahian et al, 2021), while others argued that such a link exists while treating SRL strategy use as a holistic construct (Yabukoshi, 2020;Akhmedjanova and Moeyaert, 2022). Our study has not only revealed the influence of individual-proficiency variation on the use of self-regulated writing strategies when writing reflective journals, but also paints a clear picture of where such variation lies.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Differences in the use of self-regulated writing strategies between the high-and low-proficiency groups Some previous studies on the use of reflective writing have tended to hypothesize a potential influence of individual proficiency levels on observable SRL-related behaviors (Farahian et al, 2021), while others argued that such a link exists while treating SRL strategy use as a holistic construct (Yabukoshi, 2020;Akhmedjanova and Moeyaert, 2022). Our study has not only revealed the influence of individual-proficiency variation on the use of self-regulated writing strategies when writing reflective journals, but also paints a clear picture of where such variation lies.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding change over time in self-regulated writing strategies, SRL theory itself emphasizes the central role of time and ordered SRL sequencing during the writing process (Zimmerman, 2008;Zimmerman and Schunk, 2011), and that students' journey to adopting such strategies may be quite lengthy (Akhmedjanova and Moeyaert, 2022). Therefore, it is important to trace developmental patterns in students' use of them.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations